The Production of ignorance about science: an analysis of the relationship between propaganda, the climate emergency and information ethics - Barros, Carlos Eduardo (Cadernos de Astronomia, 2025)
Despite an apparent consensus on the strategic value of science for society and the material gains that the development of research and technologies brings to industry, culture and power relations, there is an important debate about the influence of external political and economic values on scientific knowledge. Using the conceptual perspective of agnotology, this article analyzes how propaganda campaigns use the information ethics of digital platforms to produce and disseminate doubt and ignorance about scientific knowledge of anthropogenic climate change and its spokespeople. Based on a literature review, we reinforce the warning of astrophysicists, geologists, sociologists and many other scientists about how the idea of a “neutral science” weakens the community and fuels denialism. We observe the main strategies and discourses that combat the consensus on the climate emergency and its relationship with an unsustainable economic model of exploitation of the planet’s resources, pointing out the responsibilities of the oil industry, agribusiness and big tech in this scenario.
Keywords: climate emergency; disinformation; information ethics